Pemberdayaan Masyarakat melalui Pelatihan Pembuatan Kerajinan Tangan Dari Bahan Rosok - Ulifatul M'rifah; Zhifana Hanum Agustia; Maula Lailatul Fitria; Alifah Nur Hidayah; Mohamad Ma’mun (LP3M IAIFA Kediri, 2024)
Waste is a very crucial problem in Indonesia, from organic waste to non-organic waste. According to data presented by the Ministry of Environment and Forestry, it is shown that Indonesia produces more than 67 million tons of waste every year, most of which is still not managed properly. This can hurt the environment, public health, and overall quality of life. Seeing these problems, a more innovative and environmentally friendly solution is needed to manage waste in Tegowangi Village. One solution that can be implemented is the Rosok Alms Movement. This activity aims to provide new skills in processing rosok waste into economically valuable crafts and also to reduce the amount of waste produced, but also to empower the community through training in making handicrafts from rosok materials. The method or approach used in this training is the ABCD method or Asset-Based Community Development, where this method is a sustainable empowerment method that is based on the assets, strengths and potential of the community. The targets of this training are housewives and Muslim women from Tegowangi village. The result of this training is a bag made from plastic cups that have been wrapped using colored rope and put together to form a bag. Apart from that, there are also bags made from coffee sachet wrappers that are woven to form a bag.